IRF1 Maintains Optimal Constitutive Expression of Antiviral Genes and Regulates the Early Antiviral Response - Panda, Debasis; Gjinaj, Erisa; Bachu, Mahesh; Squire, Erica; Novatt, Hilary; Ozato, Keiko; Rabin, Ronald L. (Frontiers in Immunology, 2019)
Viral defense at mucosal sites depends on interferons (IFN) and IFN stimulated genes (ISGs), either of which may be constitutively expressed to maintain an “antiviral state (AVS). However, the mechanisms that govern the AVS is poorly defined. Using a respiratory epithelial cell line deficient in IRF1, we demonstrate higher susceptibility to infection with vesicular stomatitis virus (VSV) and influenza. IRF1-mediated restriction of VSV is IFN-independent, as IRF1 regulates constitutive expression of ~250 genes, including four antiviral ISGs: MX1, OAS2, BST2 and RNASEL, Additionally, IRF1 enhances rapid expression of IFNβ and IFNλ after stimulation with poly I:C and regulates ISG expression. Mechanistically, IRF1 enhances recruitment of BRD4 to promotor-enhancer regions of ISGs for rapid expression and maintain optimal levels of histone H3K4me1 for optimal constitutive expression. Taken together, IRF1 enhances three aspects of antiviral defenses: the constitutive AVS, IFN expression and downstream expression of anti-viral ISGs.